Theology as conversation: the significance of dialogue in historical and contemporary theology : a Festschrift for Daniel L. Migliore - McCormack, Bruce L. (Eerdmans, 2009)
Foreword / Kimlyn J. Bender and Bruce L. McCormack -- Engagements with the theology of Karl Barth, Christ and canon, theology and history : the Barth-Harnack dialogue revisited / Kimlyn J. Bender -- Argue theologically with one another : Karl Barth's argument with Emil Brunner / Gerhard Sauter -- God's being is his own decision : the Jüngel-Gollwitzer "debate" revisited / Bruce L. McCormack -- The time that remains : Hans-Georg Geyer in the intellectual debate about a central question in the twentieth century / Gerrit Neven -- Echoes of Barth in Jon Sobrino's critique of natural theology : a dialogue in the context of post-colonial theology / Matthew D. Lundberg -- "Beautiful playing" : Moltmann, Barth, and the work of the Christian / Cynthia L. Rigby -- Conversations with traditional theological topics "inspired heterodoxy" : the freedom of theological inquiry and the well-being of the church / Dawn DeVries -- What is the meaning of revelation? : H. Richard Niebuhr, modernism, and nicene Christianity / George Hunsinger -- Interpretatio in bonem partem : Jürgen Moltmann on the immanent Trinity / Thomas R. Thompson -- God's body or beloved other? : Sallie McFague and Jürgen Moltmann on God and creation / David J. Bryant -- In search of a non-violent atonement theory : are Abelard and Girard a help or a problem? / Gregory Anderson Love -- The people of God in Christian theology / Katherine Sonderegger -- Will all be saved or only a few? : a dialogue between faith and grace / Jürgen Moltmann -- Wholly called, holy callings : questioning the secular/sacred distinctions in vocation / Stephen L. Stell -- Theological identity : a dance of loyalty / Kathleen D. Billman -- Luther's ghost : ein gluehender backofen voller liebe / George Newlands -- Theology in dialog with society and culture : which forms and themes should Christian theology uphold in dialog with secular culture? / Michael Welker -- Faith in the public square / David Fergusson -- Reading for preaching : the preacher in conversation with story-tellers, biographers, poets, and journalists / Cornelius Plantinga, Jr. -- Charles Hodge as a public theologian / John Stewart